On Some Guiding Principles of Enacting Mathematical Problem Solving for Classroom Instruction - Ng, Yu Xin; Lam, Toh Tin (Universitas Muhammadiyah Purwokerto, 2024)
In addressing the key role that problem solving has been playing in mathematics instruction for K-12, this paper aims to assist mathematics teachers and educators to consider a set of guiding principles for designing problem solving tasks for classroom instructions. The set of guiding principles was synthesized and proposed through the researchers’ systematic review of existing education literature on problem solving.